Global and local environmental and energy advantages of a geothermal heat pump interacting with a low temperature thermal micro grid. (15th September 2018) - Marrasso, E.; Roselli, C.; Sasso, M.; Tariello, F.
Highlights: Effects of a low temperature grid based-system on urban heat island are analyzed. Global environmental analysis assesses equivalent carbon dioxide emission reduction. Local environmental analysis is performed to assess the air temperature increase. A sensitivity analysis is considered to estimate the maximum temperature growth. Dynamic simulations are performed to carry out energy and environmental analyses. Abstract: Urban heat island affects cities climate and results in higher air temperature with respect to the surrounding rural zones. Anthropogenic heat released by human activities exacerbates this phenomenon which impacts on environmental and energy fields. Air conditioning is commonly used to achieve comfort indoor conditions in the warmer urban climate but it is also one of the serious cause of the urban heat islands. The heat rejected by the condensers of air conditioning systems, increases the air temperature next to the buildings in which they are installed. In this paper a system consisting of a ground-source heat pump, a low temperature thermal network and a series of electric heat pumps, is analysed. The thermal grid is the heat source/sink for the water to water electric heat pumps that are installed at each end-user of a multi-purpose six floors building located in Naples (Southern of Italy). In cooling mode the condenser heat is discarded in the ground by the ground source heat pump that operates between the lower temperature thermal grid and the borefield. In the heating period the thermal network is heated by the ground source heat pump, that draws energy from the ground. The models simulating the energy conversion systems, the low temperature thermal network and the building, are implemented in the dynamic simulation software TRNSYS 17. A first advantage of the proposed configuration is the avoided interaction with the outside air and the corresponding mitigation of the urban heat island phenomenon. A second one is the higher coefficient of performance of the water to water electric heat pumps, operating with a lower temperature gap with respect to the case in which the electric heat pumps interact with the outside air. Furthermore, the interaction with thermal grid allows high seasonal performance due to the low fluctuation of the temperature with respect to the air. Finally this energy efficient system could be simply installed not only in the new buildings, but also in refurbishments. The proposed system is compared with a conventional one installed in each dwelling consisting of an air to water air conditioner for cooling operation and a boiler for heating. Interesting global and local environmental advantages are obtained.